2017
DOI: 10.1186/s12939-017-0620-0
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of equity in the distribution of non-financial health care inputs across public primary health care facilities in Tanzania

Abstract: BackgroundThere is limited evidence on how health care inputs are distributed from the sub-national level down to health facilities and their potential influence on promoting health equity. To address this gap, this paper assesses equity in the distribution of health care inputs across public primary health facilities at the district level in Tanzania.MethodsThis is a quantitative assessment of equity in the distribution of health care inputs (staff, drugs, medical supplies and equipment) from district to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It could be argued that lower HIV testing service use amongst women living in rural areas, could be related to unequal access to society's resources that include education, employment and health care services [60][61][62][63][64] and existing systematic socioeconomic disparities between urban-rural dwellers. Additionally, increased stigma and discrimination in rural communities [65] and shortages of qualified health professionals and supplies in the rural health facilities [60,66] may lead to lower utilization of HIV testing services amongst pregnant women from rural areas. This suggests that strategies targeting rural areas must be strengthened to reduce barriers to prenatal HIV testing for PMTCT of HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be argued that lower HIV testing service use amongst women living in rural areas, could be related to unequal access to society's resources that include education, employment and health care services [60][61][62][63][64] and existing systematic socioeconomic disparities between urban-rural dwellers. Additionally, increased stigma and discrimination in rural communities [65] and shortages of qualified health professionals and supplies in the rural health facilities [60,66] may lead to lower utilization of HIV testing services amongst pregnant women from rural areas. This suggests that strategies targeting rural areas must be strengthened to reduce barriers to prenatal HIV testing for PMTCT of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Meaningfully, more than 90% of women in this study reported that their pregnancy was planned and of those, approximately 75% had been tested for HIV. Furthermore, educated women are more likely to make decisions to seek health care [69] and reside in urban areas where there is easier access to health facilities that provide quality PMTCT of HIV services [63,66].…”
Section: Discussionmentioning
confidence: 99%
“…Health system infrastructure ranges from the physical facilities, information systems to medical equipment and also involves construction of new infrastructure as a strategy to achieving UHC [4]. To provide quality health services required for universal health coverage, health facilities should be structured to meet health care needs and equipped with utilities such as electricity, water and skilled health workforce and also to construct or renovate primary health facilities that are able to offer quality services [5,6]. Furthermore, improvement in geographical access of health services provision through strategic infrastructure development strengthens the referral system, increase service utilization and, in so doing, improve health outcome indicators at individual and community level.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate and equitable financing remains a challenge for many low income country health systems', constraining access to services of sufficient quality [1][2][3][4][5]. As a result, some countries have embarked on a series of reforms to raise additional revenue [1][2][3][4][5][6], change how services are paid for, as well as how funds flow through the system and are managed. Decentralisation of financial management from central or local government level to facility level is one among many reforms that are gaining popularity in a number of African countries and has been found to increase the availability and accessibility of funds at the service delivery level [7,8].…”
Section: Introductionmentioning
confidence: 99%